(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Climate change’s political economic strategy is an approach to research the key problems of climate change decision-making from a political economy that thinks of public or political mechanisms. The growing knowledge and urgency of climate change has pressured researchers to learn more about the many players and influences that impact the negotiations on climate change and explore more successful ways to combat climate change. Climate Change is now a commonly believed reality, first and foremost a political question.